POSTPARTUM BLUES PADA IBU POSTPARTUM PRIMIPARA - Desi Ari Madi Yanti, Desi Ari Madi Yanti (Patria Artha Journal of Nursing Science, 2017)
The phenomenon of the occurrence of postpartum blues on the first or third births less attention primarily by nurses , postpartum blues was considered as mild and temporary mental disorder that disappears within a few days postpartum . The purpose of this research is to identify the determinant factors on the occurrence of postpartum blues postpartum primiparous mothers . This research is a quantitative study that uses a cross-sectional design with consecutive sampling with a sample of 100 people . In this study showed that all mothers experience postpartum blues postpartum where the most influential factor for the occurrence of postpartum blues is aged with p value = 0.006 . Age < 20 years of age who are not yet ready to be a mother so it is difficult to adapt to both the physical aspects like fatigue often experienced in caring for the baby , while the psychological aspect , the mother was not ready to undergo a new role . Postpartum blues screening is recommended for all pregnant women and postpartum mothers , and make home visits to determine the circumstances in order to reduce the incidence of postpartum maternal postpartum blues. maternal postpartum primiparous , postpartum blues